2007
DOI: 10.1128/aac.01506-06
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Penicillin G in Very-Low-Birth-Weight Neonates

Abstract: Data on the pharmacokinetics (PKs) of penicillin G (PEN) in neonates date back to the 1970s and do not include data for very-low-birth-weight (VLBW) neonates. The aim of this study was to describe the steady-state PKs and to establish an optimal regimen for the dosing of PEN in neonates with gestational ages of less than 28 weeks and birth weights of less than 1,200 g. Two PEN dosing regimens were studied: 50,000 IU (30 mg)/kg of body weight every 12 h (q12h) (group 1; n ‫؍‬ 9) and 25,000 IU (15 mg)/kg q12h (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…The half-life (t ½ ) decreased from 3.2 h in the first week of life to 1.4 h in week 3. A study in 18 very low birth weight (VLBW) neonates confirmed that the t ½ in VLBW neonates is longer (4.2 h), and these authors concluded that 15 mg kg −1 12 h −1 results in serum concentrations above the minimum inhibitory concentration for 90% of group B streptococci strains (MIC 90 ) [6].…”
Section: Benzylpenicillin (Penicillin G)mentioning
confidence: 91%
See 1 more Smart Citation
“…The half-life (t ½ ) decreased from 3.2 h in the first week of life to 1.4 h in week 3. A study in 18 very low birth weight (VLBW) neonates confirmed that the t ½ in VLBW neonates is longer (4.2 h), and these authors concluded that 15 mg kg −1 12 h −1 results in serum concentrations above the minimum inhibitory concentration for 90% of group B streptococci strains (MIC 90 ) [6].…”
Section: Benzylpenicillin (Penicillin G)mentioning
confidence: 91%
“…There have been three separate studies on benzylpenicillin (penicillin G) [5][6][7] ( Table 1). The first detailed study of the PK of penicillin in neonates [5] was performed in the early 1970s in 47 newborn infants (no details are given of the gestation except that the group included both preterm and term neonates).…”
Section: Benzylpenicillin (Penicillin G)mentioning
confidence: 99%
“…The control group consisted of 35 gestational age-, postnatal age-and birth weight-matched neonates who had not participated in a PK study. Results: We did not observe significant differences in 112 that extra blood loss of up to 2.3 ml/kg over 12 h due to participation in a pharmacokinetic (PK) study [3] does not exert adverse influence on hemodynamic stability and/or increase the risk of complications in VLBW neonates.…”
Section: Introductionmentioning
confidence: 99%
“…1,200 g and aged ! 5 days, needing treatment with penicillin-G and gentamicin for risk of early onset sepsis [3] .…”
Section: Patient Populationsmentioning
confidence: 99%
See 1 more Smart Citation